Atributos bioquímicos e índice de qualidade do solo em áreas mineradas em recuperação na Amazônia Oriental - Silva, Letícia Coelho Vaz (2021)
The Carajás National Forest (FLONA), located in the Brazilian Amazon, contains an important and abundant mineral province, with reserves containing levels above 65% of Fe. However, mining activity has intensified the loss of native forest areas, and the revegetation of mined areas must meet legal requirements. Revegetation promotes direct and indirect benefits to the soil, including: the introduction of C to the system, nutrient cycling, CO2 sequestration and a progressive increase in ecosystem services, with a greater presence of processes mediated by soil microorganisms. This study aimed to investigate the responses of microbial community biomass and activities to the effects of revegetation, and to understand the effects of soil abiotic factors on these responses. Therefore, four rehabilitation chronosequences under the influence of Fe mining in FLONA Carajás, PA, eastern Brazilian Amazon were evaluated. Soil samples were collected in Sandstone II, Northwest II and South IV and analyzed in 2016, 2017, 2018 and 2019. The collected soil was submitted for chemical characterization, texture and microbiological analysis. Microbial biomass carbon, basal respiration, metabolic quotient, soil protein related to easily extractable glomalin and soil enzymatic activities (β-glucosidase, acid phosphatase, urease and fluorescein diacetate hydrolysis) were evaluated. The data were submitted to analysis of variance (ANOVA), Tukey test (p<0.05) and principal component analysis (PCA). The technique of order of preference by similarity with an ideal solution (TOPSIS) was also applied to generate soil quality indices (SQI) of the chronosequences based on selected variables, in 2016 and 2018. The IQS results were submitted to analysis of variance (ANOVA) and Tukey's test (p<0.05), and Pearson's correlation was applied between variables, the revegetation time and the IQS. An increase in MBC was observed over the chronosequences and over the years of collection. A gain in soil microbial activity was also identified, reflected by the SBR, β- Glu, Ure, Phos and FDA variables. The PCA and SQI analysis showed that intermediate and advanced stages are close to the native reference areas, with microbiological indicators being the main factors influencing the SQI. Among chemical attributes and texture, Fe and P showed greater influence on SQI. The results obtained indicate the rehabilitation of revegetated areas, especially those in intermediate and advanced stages, which are close to the reference conditions. It was possible to verify the return of ecological processes and functions performed by soil microorganisms in the chronossequences, contributing to the success of the rehabilitation.